Acardius amorphous acephalus: report of a case - Herrera, César (2015)
Amorphus humans twins, Chorangiopagus parasiticus or twin reversed arterial perfusion, are rare abnormalities that occur in monozygotic multiple pregnancies. It is proposed artery-artery or vein to vein anastomosis anomalies in a monozygotic placenta, the blood is perfused from the hemodynamic active twin (pump twin) to the other (receptor twin). Inadequate perfusion to the receptor twin is the cause of anomalies, including acardia and anencephaly. The pump twin is structurally normal, but has a risk to present congestive cardiac failure in utero and without treatment, 50 to 75% of the cases die, particularly if the receptor twin weighs more than half the pump twin. We present a case of a 30 year-old woman with postnatal diagnosis of an acephalus, amorphous acardius fetus.